Effect of Oral Administration of Royal Jelly towards Fertility Performance of Rabbit through Artificial Insemination - Tan, Y J Y; Wakil, A M; Sukri, S A Mohamad; J Stephen; Khalif, R I A Raja (Animal Reproduction Update, 2025)
The rabbit livestock industry is rising rapidly as an alternative protein source in Malaysia. As the global population increases, alternative food sources such as rabbit-based products are important for meeting human demand for livestock products. Optimization of rabbit production relies on reproductive technology. Assisted reproduction technologies (ART) like artificial insemination (AI) are being introduced to the farmer to maximize the production of the rabbit industry. However, local livestock farmers still need to improve their knowledge and technique. Thus, this study aims to investigate the fertility rate of does using artificial insemination compared to natural mating (NM) and to determine the effect of different concentrations of oral administration of royal jelly (RJ) on semen fertility in rabbits. A total of 12 bucks and 20 does of American White rabbits (Oryctolagus cuniculus) were used, with ages between 7 to 12 months and average body weights of 2.5 to 3 kg. The bucks were assigned to 4 experimental groups for oral administration: (a) control A, 0 mg/kg of royal jelly; (b) control B, 0 mg/kg of royal jelly; (c) treatment 1, 100 mg/kg of royal jelly; and (d) treatment 2, 50 mg/kg of royal jelly. Control A rabbit was mated naturally, while the other groups were mated using AI. Sperm quality was evaluated through physical criteria: volume, colour, pH, odour, and viscosity. Pregnancy diagnosis (manual abdominal palpation, real-time ultrasound) was performed to evaluate the conception rate of the doe. The result that the conception rate of natural mating (83.33%) was higher compared to artificial insemination (16.13%). Moreover, oral administration of royal jelly showed a negative effect on the conception rate of does, where 0 mg/kg of royal jelly showed 36.36%, 100 mg/kg showed 0%, and 50 mg/kg showed 10% of conception rate.